Sāḥir Ludhiyānvī - Fāt̤mī, ʿAlī Aḥmad (Maġribī Bangāl Urdū Akāḍmī, 2021)
On the life and works of Sāḥir Ludhiyānvī, 1921-1980, Urdu poet.
Der Paralleltitel ist eine Umschrift von der Rückseite der Haupttitelseite und dem hinteren Buchumschlag
Keywords: Sāḥir Ludhiyānvī; 1921-1980; Criticism and interpretation.